Interaction of Neisseria meningitidis with Human Dendritic Cells - Kolb-Mäurer, Annette (American Society for Microbiology, 2001)
Infection with Neisseria meningitidis serogroup B is responsible for fatal septicemia and meningococcal meningitis. The severity of disease directly correlates with the production of the proinflammatory cytokines tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-1), IL-6, and IL-8. However, the source of these cytokines has not been clearly defined yet. Since bacterial infection involves the activation of dendritic cells (DCs), we analyzed the interaction of N. meningitidis with monocyte-derived DCs. Using N. meningitidis serogroup B wild-type and unencapsulated bacteria, we found that capsule expression significantly impaired neisserial adherence to DCs. In addition, phagocytic killing of the bacteria in the phagosome is reduced by at least 10- to 100-fold. However, all strains induced strong secretion of proinflammatory cytokines TNF-α, IL-6, and IL-8 by DCs (at least 1,000-fold at 20 h postinfection [p.i.]), with significantly increased cytokine levels being measurable by as early as 6 h p.i. Levels of IL-1β, in contrast, were increased only 200- to 400-fold at 20 h p.i. with barely measurable induction at 6 h p.i. Moreover, comparable amounts of cytokines were induced by bacterium-free supernatants of Neisseria cultures containing neisserial lipooligosaccharide as the main factor. Our data suggest that activated DCs may be a significant source of high levels of proinflammatory cytokines in neisserial infection and thereby may contribute to the pathology of meningococcal disease.